A column generation technique for routing and spectrum allocation in cloud-ready survivable elastic optical networks - Goścień, Róża; Walkowiak, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Driven by increasing user requirements and expectations, the fast development of telecommunications networks brings new challenging optimization problems. One of them is routing and spectrum allocation (RSA) of three types of network flows (unicast, anycast, multicast) in elastic optical networks (EONs) implementing dedicated path protection (DPP).
Keywords: elastic optical network; anycast traffic; multicast traffic; network survivability; column generation technique